2010
DOI: 10.1016/j.ydbio.2009.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Fgf8b-containing spliceforms, but not Fgf8a, are essential for Fgf8 function during development of the midbrain and cerebellum

Abstract: Summary The single Fgf8 gene in mice produces eight protein isoforms (Fgf8a–h) with different N-termini by alternative splicing. Gain-of-function studies have demonstrated that Fgf8a and Fgf8b have distinct activities in the developing midbrain and hindbrain (MHB) due to their different binding affinities with FGF receptors. Here we have performed loss-of-function analyses to determine the in vivo requirement for these two Fgf8 spliceforms during MHB development. We showed that deletion of Fgf8b-containing spl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…In chick embryos, FGF8-coated beads can induce an ectopic ISO and cerebellum, or, in caudal forebrain, a striking morphological duplication of the midbrain (Crossley et al, 1996; Martinez et al, 1999). Conditional deletion of Fgf8 , or specific deletion of the FGF8b isoform in mice causes loss of the midbrain, isthmus, and cerebellum (Chi et al, 2003; Guo et al, 2009). Similarly, ectopic FGF8 in the early NP induces neocortical area duplications, and augmenting or reducing the endogenous source of FGF8 causes appropriate R/C area shifts in the map (Fukuchi-Shimogori and Grove, 2001; Garel et al, 2003), including major patterning changes in the frontal cortex immediately adjacent to the endogenous FGF8 source (Garel et al, 2003; Cholfin and Rubenstein, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In chick embryos, FGF8-coated beads can induce an ectopic ISO and cerebellum, or, in caudal forebrain, a striking morphological duplication of the midbrain (Crossley et al, 1996; Martinez et al, 1999). Conditional deletion of Fgf8 , or specific deletion of the FGF8b isoform in mice causes loss of the midbrain, isthmus, and cerebellum (Chi et al, 2003; Guo et al, 2009). Similarly, ectopic FGF8 in the early NP induces neocortical area duplications, and augmenting or reducing the endogenous source of FGF8 causes appropriate R/C area shifts in the map (Fukuchi-Shimogori and Grove, 2001; Garel et al, 2003), including major patterning changes in the frontal cortex immediately adjacent to the endogenous FGF8 source (Garel et al, 2003; Cholfin and Rubenstein, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Further SPR analysis showed that recombinant mouse Fgf8a and Fgf8b, the two biologically active Fgf8 isomorphs (44,45), bound in a Ca 2ϩ -dependent manner and with equally high affinity to a purified Cubn chip (Fig. 5B).…”
Section: Arrows) E and Eј Fgf8 Is Normally Expressed In The Commissmentioning
confidence: 99%
“…Fgf8 isoforms (of which Fgf8b is the major form) are co-expressed many tissues in the embryo, including the gastrula, the mesoderm, the midbrain-hindbrain boundary and the limb bud apical ectodermal ridge (Crossley et al ., 1995). Interestingly, elimination of the Fgf8a -containing spliceforms ( a, c, e, g ) in mouse, through gene targeted alteration of the relevant splice acceptor site, failed to cause embryonic defects in Fgf8 -expressing tissues (Guo et al ., 2010), in contrast to deletion of the b -containing forms or complete Fgf8 nulls. Additionally, compound mutants of Fgf8a and Fgf17 , which likely has Fgf8a-like activity, did not result in additional defects (Guo et al ., 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, elimination of the Fgf8a -containing spliceforms ( a, c, e, g ) in mouse, through gene targeted alteration of the relevant splice acceptor site, failed to cause embryonic defects in Fgf8 -expressing tissues (Guo et al ., 2010), in contrast to deletion of the b -containing forms or complete Fgf8 nulls. Additionally, compound mutants of Fgf8a and Fgf17 , which likely has Fgf8a-like activity, did not result in additional defects (Guo et al ., 2010). Residual Fgf8a-like activity could be supplied by Fgf18 in these animals, but triple mutants have not been described.…”
Section: Discussionmentioning
confidence: 99%